Analisis Faktor Pendorong dan Penarik yang Mempengaruhi Keputusan Konsumen Membeli Produk Pertanian di Modern Market Kota Palembang - Meirisa, Dina; Arafah, Elmeizy; Rakhmat, Acip (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the factors that influence consumers to decide to buy vegetables in modern markets in Palembang City. It also explores the pull and push factors that drive consumer purchasing decisions in these markets. Method: This research uses both quantitative and qualitative analytical methods. The data were tested using validity and reliability tests, as well as F-test (simultaneous significance) and t-test (partial significance) in multiple linear regression analysis. Results: The regression analysis resulted in a constant value of 0.343, indicating that when price, income, and lifestyle scores are zero, the purchase decision score remains at 0.343. The regression coefficient for the price variable (X1) was 0.375, suggesting a positive relationship between price and purchase decisions. This implies that for every one-unit increase in price (with other variables held constant), the likelihood of purchasing decisions increases by 0.375 units. Conclusions: Price, income, and lifestyle significantly influence consumers' decisions to buy vegetables in modern markets in Palembang. Among these, price has the strongest influence, indicating that affordability remains a critical factor in consumer choice. Limitations: This study is limited to 160 female and young consumers selected through purposive sampling, which may not fully represent the broader population of vegetable buyers in Palembang. Contribution: This research contributes to understanding consumer behavior in urban retail environments and provides valuable input for modern market managers in developing pricing and marketing strategies to attract vegetable buyers.